Safer solid‐state lithium metal batteries: Mechanisms and strategies - Yang, Shi‐Jie; Hu, Jiang‐Kui; Jiang, Feng‐Ni; Yuan, Hong; Park, Ho Seok; Huang, Jia‐Qi (InfoMat, 2024)
Solid‐state batteries that employ solid‐state electrolytes (SSEs) to replace routine liquid electrolytes are considered to be one of the most promising solutions for achieving high‐safety lithium metal batteries. SSEs with high mechanical modulus, thermal stability, and non‐flammability can not only inhibit the growth of lithium dendrites but also enhance the safety of lithium metal batteries. However, several internal materials/electrodes‐related thermal hazards demonstrated by recent works show that solid‐state lithium metal batteries (SSLMBs) are not impenetrable. Therefore, understanding the potential thermal hazards of SSLMBs is critical for their more secure and widespread applications. In this contribution, we provide a comprehensive overview of the thermal failure mechanism of SSLMBs from materials to devices. Also, strategies to improve the thermal safety performance of SSLMBs are included from the view of material enhancement, battery design, and external management. Consequently, the future directions are further provided. We hope that this work can shed bright insights into the path of constructing energy storage devices with high energy density and safety. Focusing on the safety hazards of SSLMBs, an in‐depth understanding of the thermal failure mechanisms of SSLMBs is classified and summarized from materials to devices. Beyond that, future directions in improving battery safety are also involved. This work sheds bright insights into the path of constructing energy storage devices with high energy density and safety.